Pediatric Minor Traumatic Brain Injury With Intracranial Hemorrhage: Identifying Low-Risk Patients Who May Not Benefit From ICU Admission. Issue 3 (March 2019) - Burns, Erin Comer; Burns, Beech; Newgard, Craig D.; Laurie, Amber; Fu, Rongwei; Graif, Theresa; Ward, Casey S.; Bauer, Abbie; Steinhardt, David; Ibsen, Laura M.; Spiro, David M.
Abstract : Background: Pediatric patients with any severity of traumatic intracranial hemorrhage (tICH) are often admitted to intensive care units (ICUs) for early detection of secondary injury. We hypothesize that there is a subset of these patients with mild injury and tICH for whom ICU care is unnecessary. Objectives: To quantify tICH frequency and describe disposition and to identify patients at low risk of inpatient critical care intervention (CCI). Methods: We retrospectively reviewed patients aged 0 to 17 years with tICH at a single level I trauma center from 2008 to 2013. The CCI included mechanical ventilation, invasive monitoring, blood product transfusion, hyperosmolar therapy, and neurosurgery. Binary recursive partitioning analysis led to a clinical decision instrument classifying patients as low risk for CCI. Results: Of 296 tICH admissions without prior CCI in the field or emergency department, 29 had an inpatient CCI. The decision instrument classified patients as low risk for CCI when patients had absence of the following: midline shift, depressed skull fracture, unwitnessed/unknown mechanism, and other nonextremity injuries. This clinical decision instrument produced a high likelihood of excluding patients with CCI (sensitivity, 96.6%; 95% confidence interval, 82.2%–99.9%) from the low-risk group, with a negative likelihood ratio of 0.056 (95% confidence interval, − 0.053–0.166). The decision instrument misclassified 1 patient with CCI into the low-risk group, but would have impacted disposition of 164 pediatric ICU admissions through 5 years (55% of the sample). Conclusions: A subset of low-risk patients may not require ICU admission. The proposed decision rule identified low-risk children with tICH who may be observable outside an ICU, although this rule requires external validation before implementation.